PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN WORD OF MOUTH PENGHUNI PERUMAHAN KARYAWAN (STUDI KASUS PADA DEPARTEMEN GFS PT. VALE INDONESIA) - Topan Prasetyo; Dian Parawansa; Andi Nur Massepe (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
PT. VALE Indonesia has many employees in its area of ​​operation, approximately 3000 permanent employees owned by PT VALE Indonesia at this time.This study aims to determine the effect of service quality on satisfaction and the word of mouth resident housing employees of PT. VALE Indonesia in order to design a strategy to increase the satisfaction of residential residents who are company employees who are closely related to the company's strategy in the long term. This research method using descriptive format is a method in researching the status of a group of people, an object, a set of conditions, a system of thought, or a class of events in the present. The result of this research indicate that service quality have positive and significant influence to satisfaction, service quality have positive and significant influence to word of mouth (WOM), satisfaction of housing resident positively and significantly influences to residential resident of PT Vale Indonesia. While the quality of service and satisfaction of occupants positively and significantly affect the WOM housing residents of PT Vale Indonesia together.